Structural analysis of κ-carrageenan sulfated oligosaccharides by positive mode Nano-ESI-FTICR-MS and MS/MS by SORI-CID - Aguilan, Jennifer T (Archīum Ateneo, 2006)
Structural analysis of sulfated oligosaccharides from κ-carrageenan of up to ten residues (MW >2 kDa) was successfully carried out by positive mode nano-ESI-FTICR-MS together with MS/MS using sustained off-resonance irradiation-collision induced dissociation (SORI-CID). Glycosidic bond cleavage reactions via the B- and Y-types of fragmentation were observed and enabled complete sequencing of the oligosaccharide samples. The positions of the labile sulfate substituents were observable using SORI-CID, enabling the determination of the sequence of the sulfated residues.